Cultural Legitimacy and Political Identity: Traditional Titles in Electoral Politics, Lampung, Indonesia - Gita Paramita Djausal; Fitri Juliana Sanjaya; Lilih Muflihah; Rizky Bayu Pamungkas (Politicon : Jurnal Ilmu Politik, 2025)
Indonesia has a diverse range of cultures that enable individuals to utilize their cultural identity as a representation of their values in politics. This study analyzes the role of customary law in local politics in Lampung as a cultural legitimacy strategy for expanding the electoral base. Data from mass media between 2020 and 2024 indicate that 15 traditional title conferral ceremonies were held for 26 political figures at both local and national levels. Based on this dataset, a media content analysis was conducted, focusing on four key elements: the recipients’ names, their status or political positions, the customary titles they received, and the authorities conferring these titles. The conferral process serves as a cultural legitimization strategy, enabling political candidates to present themselves as figures who understand and respect local values and traditions. In relation to the legislative elections, regional head elections, and the presidential election, these events reveal a tendency for political activities to be closely associated with individuals who receive traditional titles. This phenomenon represents the articulation of social and cultural capital in political dynamics, aiming to expand the electoral base. However, this reality also presents a critical challenge, especially in maintaining the authenticity of customary traditions so that they do not become merely a pragmatic instrument in political contestation. Therefore, regulations and cultural awareness are necessary to preserve the essence of tradition, ensuring it remains an integral part of society.